Logan Medallist 9. Geological Studies in the Northern Appalachian Orogen – Past, Present, and Future - Barr, Sandra M. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2024)
The northern Appalachian orogen played a pivotal role in early geological studies of mountain belts. Its 100-year global influence as the “type area” for the Hall-Dana geosynclinal theory aptly changed focus with Tuzo Wilson’s classic 1966 paper that posed (and answered) the question “Did the Atlantic Close and Then Re-open?” and led to the modern view of global tectonics based on the “Wilson Cycle”. In retrospect, these early ideas about mountain-building were much hindered by lack of factual details. The 1978 map of the Appalachian Orogen compiled and hand-drawn by Harold Williams and his students was and remains an outstanding example of geological artwork, although the actual complexity of the orogen that it depicts was barely imagined. However, the tectonic elements and along-orogen correlations that it established still form the essence of our current models, but now supported by an abundance of geological information collected steadily during the last decades of the 20th century and then accelerated by technological advances during the past 25 years. Examples include the Global Positioning System to provide accurate locations, enhanced geochemical and geophysical methods, computers and the Internet in general, and the development of accurate and precise absolute dating techniques, especially U–Pb dating of zircon. Appalachian studies now cover a spectrum from small areas investigated in detail to orogen-wide and global-scale interpretations that track Appalachian components back to their origins. We now know orders of magnitude more about the orogen than anyone could have imagined in 1978. Not surprisingly all that new knowledge has resolved many of the questions that were being asked in the 1970s but also not surprisingly, many more questions have arisen. It seems that every new map, new interpretation, or new model challenges us with new questions. It appears unlikely that geoscientists will ever be able to sit back and say “All done. We understand everything”.